Clinical applications of Lung Ultrasound in children in Pediatric Emergency Setting: a lesson from a child with severe heart disease - De Rose, Cristina; Buonsenso, Danilo; De Rosa, Gabriella; Chiaretti, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Rheumatic Heart Disease (RHD) often evolves in congestive heart failure with development of pulmonary edema after a period of asymptomatic, latent phase. In the last years, Lung Ultrasound (LUS) has gained a primary role in the diagnosis and management of pleuropulmonary disorders, also in pediatric practice and in the diagnosis and follow-up of pulmonary edema through the qualitative analysis of ultrasound B-lines.Aim of this case report is that to keep high clinicians’ attention to the diagnosis that of Rheumatic Heart Disease also in high-income countries and to deepen the role and importance of lung ultrasound, in clinical practice, in diagnosis and follow-up of pediatric lung diseases, especially in emergency settings as happened in our case. Methods: We present the case of a 14-year-old Italian boy from a medium-low socio-economic and cultural class Italian family, who was diagnosed with severe and advanced stage RHD, which had remained undiagnosed until then. Results and Conclusions: In the diagnostic process of our case, LUS played a fundamental role because it quickly directed us, contextually to the clinical and anamnestic evaluation, towards the right diagnosis, in a Pediatric Emergency Department. In clinical practice, the only LUS findings and the only qualitative analysis of the B-lines, does not make clinicians able to make a clear characterization yet. Thus the study of cardiovascular function, laboratory parameters, anamnestic and clinical data continue to be useful tools to assist the LUS in the diagnostic processes of lung diseases, as was the case in our case.